Calidad de servicio y satisfacción del cliente que utiliza créditos documentarios del Banco de Crédito del Perú sucursal Iquitos, 2021 - Lozano Barbaran, Osarsip Tito (2023)
The purpose of this study is to determine the relationship that exists between the quality of the service with the satisfaction of the client who uses documentary credits, in the Banco de Crédito del Perú branch Iquitos, 2021, the quantitative level was used, non-experimental design, the investigation It was descriptive and correlational. The population is made up of 268 who use the documentary credit service of the Banco de Crédito branch Iquitos, 2021, the survey was carried out on a representative sample of the population whose total is 91 clients, the value of 0.321** and sigma (bilateral) equal to 0.002 less than the allowed range, so the proposed hypothesis is accepted. In addition, more than 50% of the people surveyed affirm that they have a "high" level; Regarding the variable quality of service and customer satisfaction, it is concluded that there is a significant and positive correlation of a weak degree between the two variables of customers who use documentary credit of the Banco de Crédito del Perú Iquitos branch, year 2021, there is no low level of service quality of the Banco de Crédito Iquitos branch, 2021 and There is no low level of customer satisfaction of the Banco de Crédito Iquitos branch, 2021.